On the differences of separation of hazardous catechol and resorcinol through tailor-made thin film composite (TFC) membranes. Issue 3 (September 2015) - Manna, P.; Brahmbhatt, H.; Sahu, D.; Ganguly, B.; Bhattacharya, A.
Abstract Hydrophobicity and binding energy from density functional theory studies were investigated for catechol and resorcinol to explain a greater degree separation through polyamide thin film composite membranes. The effects of nature of base polymer matrices were well explained by casting the membranes from polysulfone 14% (w/w) and polyether sulfone 20% (w/w) separately having same viscosity. Concentration gradient of the two polymers could not supersede the basic material property of membranes. The separation behaviour of catechol and resorcinol through thin film composite based on said polymers, it was demonstrated that thin film composite based on polysulfone is relatively more effective in terms of better separation performances of catechol (Rcatechol 96.5%, Jv 27.2 L/m2h and Rresorcinol 84.9%, Jv 27.3 L/m2h). The effect of pH on separation performances due to variation of zeta potential was revealed to be an important factor governing the performances of membranes. The separation of organics by both thin film composite membranes is lower in acidic medium (viz. catechol 5.1% and resorcinol 6.8% for thin film composite on polysulfone membrane) compared to neutral medium because of the induced positive charge of terminal pendant amino groups on membrane surface. Presence of di-cation (Mg2+) in solution affects the membrane behaviour and influencing positively the resorcinol rejection. The separation of organics for both thin film composite membranes is higher (viz. catechol 11.2% and resorcinol 1.6%, 800 mg/L MgSO4 for thin film composite based on polysulfone membrane) compared to feed without MgSO4 because of the adsorption of Mg2+ ion on membrane surface.